COMPLEX TREATMENT OF PATIENTS WITH POSTURAL PHOBIC DIZZINESS - M. V. Romanоva; E. V. Isakova; S. V. Kotov (Alʹmanah Kliničeskoj Mediciny, 2016)
A total of 25 patients with postural phobic dizziness were examined. Somatic state and neurological status were assessed, neurovisualization and stabilometric investigation were carried out as well as a neuropsychological testing using estimation scales. The efficiency of complex rehabilitation was revealed including vestibular gymnastics, stabilometric training, psychotherapy, and pharmacotherapy in correction of psychoemotional disturbances.